Perbedaan Ph Saliva Terhadap Pemakai Kontrasepsi Hormonal Pil dan Suntik pada Wanita Usia 20-40 Tahun di Kelurahan Gedawang Kota Semarang - Erni Mardiati; Ani Subekti; Endra Nastiti Donasari; Rara Oktaviani (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2020)
Hormonal contraception is one of the contraceptive tools that many interested by family planning participants. Hormonal contraceptive methods consist of pills, injections, and implants. The use of hormonal contraceptive pills and injections may alter hormonal conditions in the periodontal tissues of contraceptive users who may cause gingival inflammation. The content of estrogen and progesterone contained in hormonal contraceptives will affect salivary pH. The purpose of this study was to observe the difference of salivary pH to users of hormonal contraceptive pill and injection in women aged 20-40 years in gedawang semarang. This study used analytical descriptive method withapproach cross sectional. The number of samples in this study are as many as 40 people with purposive sampling sampling technique. Data analysis was done by univariate and bivariate analysis. To know the difference using thetest mann-Whitney.statistical results Mann-Whitney showed that there was a significant difference between salivary pH of users of hormonal contraceptive pill and injection in women aged 20-40 years, with p-value 0,000 (p 0.005). This is due to the estrogen and progesterone content that gives effect to the costostics contained in hormonal contraceptive pill while in contraceptive hormonal inject only estrogen alone. The results of this study indicate a difference in salivary pH in users of hormonal contraceptive pills and injections. Users of hormonal contraceptive pills have an average pH of neutrality compared to users of acid-induced injectable hormonal contraceptives.